Polyvinyl chloride resin with low ultraviolet light absorption and preparation method thereof
By integrating pretreated porous adsorbent materials during PVC polymerization, the resin achieves reduced UV absorption, addressing the medical PVC resin's UV performance gap and meeting national standards.
Patent Information
- Application Number
- CN202411460005.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-27
AI Technical Summary
Existing polyvinyl chloride (PVC) resins do not meet the low ultraviolet light absorption requirements for medical applications, particularly in the wavelength range of 220nm-240nm and 241nm-350nm, as specified by national standards.
Incorporating a pretreated porous adsorbent material, such as white carbon black, zeolite, or activated carbon, during the polymerization process of PVC to reduce ultraviolet light absorption by treating the material with a modifier having a polar group, such as fatty acid amide or oxidized wax.
The resulting PVC resin exhibits significantly reduced ultraviolet light absorption, meeting the stringent medical standards for UV performance, as demonstrated by improved UV absorption values in the specified wavelength ranges.
Smart Images

Figure BDA0005091598800000111
Abstract
Description
Technical Field
[0001] The invention relates to a polyvinyl chloride resin with low ultraviolet light absorption and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is one of the five general-purpose plastics. It has good physical properties, flame retardancy and processing properties. It is also corrosion-resistant, easy to transport, and relatively cheap. It is widely used in many fields.
[0003] Medical resin is one of the common fields of polyvinyl chloride. It has direct requirements on the ultraviolet light absorption of the products, and generally requires lower UV absorption performance. For details, please refer to the national standard GB / T15593-2020 "Polyvinyl chloride plastics for blood transfusion equipment".
[0004] Therefore, this area is badly in need of a PVC resin with low ultraviolet absorption performance. Summary of the invention
[0005] The purpose of the present application is to provide a polyvinyl chloride resin with low ultraviolet absorption performance and a preparation method thereof. The ultraviolet absorption performance of the polyvinyl chloride resin is, for example, when the ultraviolet wavelength is 220nm-240nm≤0.12, 241nm-350nm≤0.07, preferably 220nm-240nm≤0.10, 241nm-350nm≤0.0.06, more preferably 220nm-240nm≤0.09, 241nm-350nm≤0.05
[0006] In one aspect, the present application provides a polyvinyl chloride resin, which can be prepared by a method comprising the following steps:
[0007] (1) providing a pretreated porous adsorbent material, wherein the pretreatment comprises treating the porous adsorbent material with a modifier having a polar group;
[0008] (2) Adding the pretreated porous adsorbent material during the polymerization of polyvinyl chloride.
[0009] On the other hand, the present application provides a method for preparing polyvinyl chloride, the method comprising the following steps:
[0010] (1) providing a pretreated porous adsorbent material, wherein the pretreatment comprises treating the porous adsorbent material with a modifier having a polar group;
[0011] (2) Adding the pretreated porous adsorbent material during the polymerization of polyvinyl chloride.
[0012] Another aspect of the present application provides a product, wherein the product is prepared from the polyvinyl chloride resin described in the present application. DETAILED DESCRIPTION
[0013] "Scope" disclosed herein is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0014] In this application, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0015] In this application, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0016] In the present application, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0017] In this application, unless otherwise specified, the terms "include" and "comprising" mentioned herein may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0018] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number itself, and "several" in "one or several" means two or more.
[0019] In the description herein, unless otherwise specified, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0020] Herein, unless otherwise specified, percentage (%) or part refers to percentage by weight or part by weight relative to the composition.
[0021] Herein, if there is no contrary description, the sum of the contents of the various components in the composition is 100%.
[0022] Herein, if there is no contrary description, the sum of the parts of each component in the composition may be 100 parts by weight.
[0023] In this context, unless otherwise specified, "a combination thereof" means a multi-component mixture of the elements described, for example a mixture of two, three, four and up to the maximum possible multi-component mixture.
[0024] If not specifically stated, the terms "a" or "an" used in the present specification means "at least one".
[0025] Herein, unless otherwise stated, all reactions are carried out at normal temperature and pressure.
[0026] In one aspect, the present application provides a polyvinyl chloride resin, which can be prepared by a method comprising the following steps:
[0027] (1) providing a pretreated porous adsorbent material, wherein the pretreatment comprises treating the porous adsorbent material with a modifier having a polar group;
[0028] (2) Adding the pretreated porous adsorbent material during the polymerization of polyvinyl chloride.
[0029] Porous materials have a large inner surface and are therefore absorbent. The inventors have found that adding porous absorbent materials during the polymerization of polyvinyl chloride (rather than adding porous absorbent materials to polyvinyl chloride resin after polymerization) can better absorb trace impurities in the polymerization of PVC and reduce the ultraviolet light absorption of the final resin. Moreover, if the porous absorbent material is pretreated with a modifier having a polar group, the ultraviolet light absorption of the resin can be more effectively reduced.
[0030] In the present application, the porous adsorption material may be a porous adsorption material commonly used in the art, including but not limited to white carbon black, zeolite (molecular sieve) and activated carbon.
[0031] White carbon black is a general term for white powdered amorphous silicic acid and silicate products, mainly referring to precipitated silica, fumed silica and ultrafine silica gel, and also including powdered synthetic aluminum silicate and calcium silicate. White carbon black is a porous substance, and its composition can be represented by SiO2·nH2O (n represents 1-10), where nH2O exists in the form of surface hydroxyl groups. The mesh size of white carbon black can be greater than or equal to 300 mesh, preferably 300-600 mesh, and more preferably 300-400 mesh.
[0032] Zeolite is a general term for zeolite family minerals, and is a hydrous alkali or alkaline earth metal aluminum silicate mineral, of which the most common ones are clinoptilolite, mordenite, chabazite, erionite, phillipsite, heulandite, lauzenite, stilbite, chabazite, calcite, natrolite and analcime, etc. The mesh size of zeolite can be 100-400 mesh, preferably 200-400 mesh, and more preferably around 300 mesh.
[0033] Activated carbon is a general term for carbon materials that are prepared by pyrolysis and activation of carbon-containing raw materials such as wood, coal and petroleum coke. It has a developed pore structure, a large specific surface area and abundant surface chemical groups, and has a strong specific adsorption capacity. In some embodiments according to the present invention, the activated carbon used may be in the form of granular activated carbon, powdered activated carbon or columnar activated carbon, preferably powdered activated carbon. The present invention can use coal-based activated carbon, wood-based activated carbon or fruit shell-based activated carbon, etc., preferably wood-based activated carbon. The mesh size of the activated carbon may be greater than or equal to 60 meshes, preferably greater than or equal to 100 meshes, and more preferably greater than or equal to 200 meshes. For example, the mesh size of the activated carbon is 60-400 meshes.
[0034] In one example of the present application, the modifier having a polar group includes fatty acid amide, fatty acid, alcohol, oxidized wax or a combination thereof.
[0035] In the present application, the fatty acid amide includes C2-C30 fatty acid amide, such as C6-C25 fatty acid amide. In an example of the present application, the fatty acid amide includes butyric acid amide, caproic acid amide, capric acid amide, dodecanoic acid (lauric acid) amide, myristic acid (myristic acid) amide, hexadecanoic acid (palmitic acid) amide, octadecanoic acid (stearic acid) amide, eicosanoic acid (arachidic acid) amide, myristoleic acid amide, palmitic acid amide, rapeseed oil amide, linolenic acid amide, linolenic acid amide, oleic acid amide or a combination thereof.
[0036] In the present application, the fatty acid includes C2-C30 fatty acid, for example C6-C25 fatty acid. In an example of the present application, the fatty acid amide includes butyric acid, caproic acid, caprylic acid, capric acid, dodecanoic acid (lauric acid), tetradecanoic acid (myristic acid), hexadecanoic acid (palmitic acid), octadecanoic acid (stearic acid), eicosanoic acid (arachidic acid), myristoleic acid, palmitoleic acid, rapeseed oleic acid, linolenic acid, linoleic acid, oleic acid or a combination thereof.
[0037] In the present application, the alcohol includes C1-C20 alkyl monoalcohol (e.g., C1-C10 alkyl alcohol, C1-C6 alkyl monoalcohol), C2-C20 alkyl diol (e.g., C2-C10 alkyl diol, C2-C6 alkyl diol), C3-C20 alkyl triol (e.g., C3-C10 alkyl triol, C3-C6 alkyl triol), C4-C20 alkyl tetraol (e.g., C4-C10 alkyl tetraol, C4-C8 alkyl tetraol) or a combination thereof. In one example of the present application, the alcohol includes methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol, butanol, butanediol, amyl alcohol, pentanediol, hexanol, hexanediol, pentaerythritol or a combination thereof.
[0038] In the present application, the oxidized wax includes oxidized paraffin (such as oxidized liquid paraffin or oxidized solid paraffin), oxidized polyethylene wax or a combination thereof.
[0039] In one example of the present application, based on 100 parts by weight of the porous adsorbent material, the amount of the modifier having a polar group is 0.05-20 parts by weight, such as 0.1-15 parts by weight, preferably 0.02-10 parts by weight, usually 0.5-5 parts by weight, and more preferably 1-2 parts by weight.
[0040] In the present application, the method of treating the porous adsorbent material with a modifier having a polar group may be a commonly used method in the art, including but not limited to mixing, ultrasound or a combination thereof. The treatment is usually carried out under heating conditions, such as 40-250°C, generally 50-200°C, preferably 60-150°C, and more preferably 80-120°C.
[0041] In the present application, the pretreated porous adsorbent material can be added to the process of preparing polyvinyl chloride, for example, it can be pre-mixed with vinyl chloride monomer and other additives and then polymerized with vinyl chloride monomer, or the pretreated porous adsorbent material can be added during the polymerization of vinyl chloride monomer. In one example of the present application, vinyl chloride monomer, initiator, solvent, polymerization aid and pretreated porous adsorbent material are added to a reactor for polymerization. The initiator can be an initiator commonly used in vinyl chloride polymerization, including but not limited to azo initiators (such as diisobutyl nitrile), organic peroxide initiators (such as benzoyl peroxide, tert-butyl hydroperoxide, etc.), inorganic peroxide initiators (such as persulfate) and redox initiators (such as hydrogen peroxide / ferrous chloride). The solvent can be a solvent commonly used in vinyl chloride monomer polymerization, including but not limited to deionized water, etc. The polymerization aid includes but is not limited to dispersants (such as organic phosphates, organic sulfur compounds, organic acids, polyolefin acids, polyvinyl alcohols or combinations thereof), pH regulators (such as sodium hydroxide, ammonium bicarbonate, sodium bicarbonate, tricalcium phosphate or combinations thereof), etc.
[0042] In one example of the present application, based on 100 parts by weight of vinyl chloride monomer, the amount of the pretreated porous adsorbent material is 0.1-20 parts by weight, such as 0.2-15 parts by weight, generally 0.5-10 parts by weight, preferably 1-5 parts by weight, and more preferably 1-2 parts by weight.
[0043] In one example of the present application, the following components are polymerized: 100 parts by weight of vinyl chloride monomer, 0.5-4.5 parts by weight of initiator, 0.25-3.0 parts by weight of dispersant, 0.01-0.05 parts by weight of buffer and 0.1-20 parts by weight of porous adsorbent. The polymerization time and temperature can be the process conditions commonly used in the art, such as 1-20 hours (generally 2-15 hours, preferably 3-15 hours, more preferably 5-10 hours) and 20-100° C. (generally 25-80° C., preferably 30-70° C.).
[0044] Another aspect of the present application provides a product, wherein the product is prepared from the polyvinyl chloride resin described in the present application.
[0045] In one example of the present application, the article includes, but is not limited to, medical products, such as medical packaging materials, medical hoses, blood storage devices, dialysis accessories, surgical gloves, and artificial organs.
[0046] Another aspect of the present application provides a method for preparing a polyvinyl chloride resin, the method comprising the following steps:
[0047] (1) providing a pretreated porous adsorbent material, wherein the pretreatment comprises treating the porous adsorbent material with a modifier having a polar group;
[0048] (2) Adding the pretreated porous adsorbent material during the polymerization of polyvinyl chloride.
[0049] For further description of the above method, please refer to the description of polyvinyl chloride resin above.
[0050] In order to make the technical means, creative features, objectives and effects of the present invention easier to understand, the present invention is further described below in conjunction with specific embodiments, but the following embodiments are only preferred embodiments of the present invention, not all.
[0051] Methods for measuring degree of polymerization
[0052] The degree of polymerization can be measured according to the national standard GB / T 3401-2007.
[0053] Example 1
[0054] First, the silica was modified by placing 100 kg silica (Degussa A300) and 1 kg stearic acid (Sven SA1801, Indonesia) into a mixing pot (Xihua small high-speed mixer XH-422-10A), physically stirring at 80°C, and taking out after 5 minutes.
[0055] After that, polyvinyl chloride was synthesized. 100 kg of vinyl chloride monomer, 0.25 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Zibo Zhenghua EHP, Shandong), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water and 2 kg of modified white carbon black were added to the polymerization reactor for stirring. After that, the temperature was raised to 57°C until the reaction was completed. The reaction time was 5.25 hours. After the reaction was completed, 3 kg of terminator (Jiahua SPJ-YC-1) was added to terminate the reaction. After drying, a PVC resin with a polymerization degree of 1000 was finally obtained, and the average polymerization degree was 1080±20.
[0056] Example 2
[0057] First, the silica was modified by placing 100 kg silica (Degussa A300) and 2 kg stearic acid (Sven SA1801, Indonesia) into a mixing pot (Xihua small high-speed mixer XH-422-10A), physically stirring at 90°C, and taking out after 5 minutes.
[0058] After that, polyvinyl chloride was synthesized. 100 kg of vinyl chloride monomer, 0.2 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water, and 3 kg of modified white carbon black were stirred in a polymerization reactor. After that, the temperature was raised to 57°C until the reaction was completed. The reaction time was 5.65h. After the reaction was completed, a terminator (Jiahua SPJ-YC-1) was added to terminate the reaction. After drying, a PVC resin with a degree of polymerization of 1000 was finally obtained, and the average degree of polymerization was 1080±20.
[0059] Example 3
[0060] First, white carbon black (Degussa A300) was modified. 100 kg white carbon black and 1.5 kg oxidized polyethylene wax (Honeywell AC316) were placed in a mixing pot (Xihua small high-speed mixer XH-422-10A), physically stirred at 100°C, and taken out after 5 minutes.
[0061] After that, polyvinyl chloride was synthesized. 100 kg of vinyl chloride monomer, 0.3 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water, and 4 kg of modified white carbon black were stirred in a polymerization reactor. After that, the temperature was raised to 57°C until the reaction was completed. The reaction time was 5.60h. After the reaction was completed, a terminator (Jiahua SPJ-YC-1) was added to terminate the reaction. After drying, a PVC resin with a polymerization degree of 1000 was finally obtained, and the average polymerization degree was 1080±20.
[0062] Example 4
[0063] First, zeolite was modified by putting 100 kg zeolite (Ningbo Jiahe New Materials, ground to 300 mesh by ourselves) and 1 kg stearic acid (Sven SA1801, Indonesia) into a mixing pot (Xihua small high-speed mixer XH-422-10A), physically stirring at 80°C, and taking out after 5 minutes.
[0064] After that, polyvinyl chloride was synthesized. 100 kg of vinyl chloride monomer, 0.25 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water, and 2 kg of modified zeolite were stirred in a polymerization reactor. After that, the temperature was raised to 57°C until the reaction was completed. The reaction time was 5.15h. After the reaction was completed, a terminator (Jiahua SPJ-YC-1) was added to terminate the reaction. After drying, a PVC resin with a degree of polymerization of 1000 was finally obtained, and the average degree of polymerization was 1080±20.
[0065] Example 5
[0066] First, zeolite was modified by putting 100 kg zeolite (Ningbo Jiahe New Materials, ground to 300 mesh by ourselves) and 2 kg stearic acid (Sven SA1801, Indonesia) into a mixing pot (Xihua small high-speed mixer XH-422-10A), physically stirring at 90°C, and taking out after 5 minutes.
[0067] After that, polyvinyl chloride was synthesized. 100 kg of vinyl chloride monomer, 0.2 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water, and 3 kg of modified zeolite were stirred in a polymerization reactor. After that, the temperature was raised to 57°C until the reaction was completed. After that, the temperature was raised to 57°C until the reaction was completed. The reaction time was 5.70h. After the reaction was completed, a terminator (Jiahua SPJ-YC-1) was added to terminate the reaction. After drying, a PVC resin with a degree of polymerization of 1000 was finally obtained, and the average degree of polymerization was 1080±20.
[0068] Example 6
[0069] First, zeolite was modified by putting 100 kg zeolite (Ningbo Jiahe New Materials, polished to 300 mesh) and 1.5 kg oxidized polyethylene wax (Honeywell AC316) into a mixing pot (Xihua small high-speed mixer XH-422-10A), physically stirring at 100 °C, and taking out after 5 minutes.
[0070] After that, polyvinyl chloride was synthesized. 100 kg of vinyl chloride monomer, 0.3 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water, and 4 kg of modified zeolite were stirred in a polymerization reactor. After that, the temperature was raised to 57°C until the reaction was completed. After that, the temperature was raised to 57°C until the reaction was completed. The reaction time was 5.70h. After the reaction was completed, a terminator (Jiahua SPJ-YC-1) was added to terminate the reaction. After drying, a PVC resin with a degree of polymerization of 1000 was finally obtained, and the average degree of polymerization was 1080±20.
[0071] Example 7
[0072] First, the activated carbon was modified by putting 100 kg of activated carbon (Shanghai Lijing Activated Carbon Co., Ltd., self-polished) and 1 kg of stearic acid (Sven SA1801, Indonesia) into a mixing pot (Xihua small high-speed mixer XH-422-10A), physically stirring at 80°C, and taking out after 5 minutes.
[0073] After that, polyvinyl chloride was synthesized. 100 kg of vinyl chloride monomer, 0.25 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water and 2 kg of modified white carbon black were stirred in a polymerization reactor. After that, the temperature was raised to 57°C until the reaction was completed. The reaction time was 5.17h. After the reaction was completed, 3 kg of terminator (Jiahua SPJ-YC-1) was added to terminate the reaction. After drying, a PVC resin with a polymerization degree of 1000 was finally obtained, and the average polymerization degree was 1080±20.
[0074] Example 8
[0075] First, the activated carbon was modified by putting 100 kg of activated carbon (Shanghai Lijing Activated Carbon Co., Ltd., self-polished) and 1 kg of stearic acid amide (Zhongjie Chemical) into a mixing pot (Xihua small high-speed mixer XH-422-10A), physically stirring at 80°C, and taking out after 5 minutes.
[0076] After that, polyvinyl chloride was synthesized. 100 kg of vinyl chloride monomer, 0.25 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water and 2 kg of modified white carbon black were stirred in a polymerization reactor. After that, the temperature was raised to 57°C until the reaction was completed. The reaction time was 5.30h. After the reaction was completed, 3 kg of terminator (Jiahua SPJ-YC-1) was added to terminate the reaction. After drying, a PVC resin with a polymerization degree of 1000 was finally obtained, and the average polymerization degree was 1080±20.
[0077] Example 9
[0078] First, the activated carbon was modified by putting 100 kg of activated carbon (Shanghai Lijing Activated Carbon Co., Ltd., self-polished) and 1 kg of pentaerythritol (Zhengzhou Hongboli Chemical Co., Ltd.) into a mixing pot (Xihua small high-speed mixer XH-422-10A), physically stirring at 80°C, and taking out after 5 minutes.
[0079] After that, polyvinyl chloride was synthesized. 100 kg of vinyl chloride monomer, 0.25 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water and 2 kg of modified white carbon black were stirred in a polymerization reactor. After that, the temperature was raised to 57°C until the reaction was completed. The reaction time was 5.30h. After the reaction was completed, 3 kg of terminator (Jiahua SPJ-YC-1) was added to terminate the reaction. After drying, a PVC resin with a polymerization degree of 1000 was finally obtained, and the average polymerization degree was 1080±20.
[0080] Comparative Example 1
[0081] Normal synthesis of polyvinyl chloride without adding any other materials. 100 kg of vinyl chloride monomer, 0.25 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate, self-prepared), and 240 kg of desalted water are stirred in a polymerization reactor. After that, the temperature is raised to 57°C until the reaction is completed. After that, the temperature is raised to 57°C until the reaction is completed. The reaction time is 5.50h. After the reaction is completed, a terminator (Jiahua SPJ-YC-1) is added to terminate the reaction. After drying, a PVC resin with a degree of polymerization of 1000 is obtained, and the average degree of polymerization is 1080±20.
[0082] Comparative Example 2
[0083] Add ordinary unpretreated silica (Degussa A300) to synthesize polyvinyl chloride. 100 kg of vinyl chloride monomer, 0.25 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Zibo Zhenghua EHP, Shandong), 0.02 kg of pH regulator (sodium bicarbonate), 240 kg of desalted water, and 2 kg of ordinary gas-phase silica are stirred in a polymerization reactor. After that, the temperature is raised to 57°C until the reaction is completed. The reaction time is 5.80h. After the reaction is completed, a terminator (Jiahua SPJ-YC-1) is added to terminate the reaction. After drying, a PVC resin with a polymerization degree of 1000 is obtained, and the average polymerization degree is 1080±20.
[0084] Comparative Example 3
[0085] Add ordinary zeolite (Ningbo Jiahe New Materials, polished to 300 mesh by yourself) without pretreatment to synthesize polyvinyl chloride. 100 kg of vinyl chloride monomer, 0.25 kg of dispersant (Kuraray L9), 0.1 kg of initiator (Shandong Zibo Zhenghua EHP), 0.02 kg of pH adjuster (sodium bicarbonate), 240 kg of desalted water, and 2 kg of ordinary zeolite are stirred in a polymerization reactor. After that, the temperature is raised to 57°C until the reaction is completed. The reaction time is 5.65h. After the reaction is completed, a terminator (Jiahua SPJ-YC-1) is added to terminate the reaction. After drying, a PVC resin with a degree of polymerization of 1000 is obtained, and the average degree of polymerization is 1080±20.
[0086] Comparative Example 4
[0087] The polymerization method is not adopted, but the pretreated silica is added after the polymerization process.
[0088] First, white carbon black (Degussa A300) was modified. 100 kg white carbon black and 1 kg stearic acid (Sven SA1801, Indonesia) were placed in a mixing pot (XH-422-10A, Xihua small high-speed mixer), physically stirred at 80°C, and taken out after 5 minutes.
[0089] Afterwards, 100 g of pretreated white carbon black was directly mixed with 4 kg of PVC resin obtained in Comparative Example 1 in a mixing pot (Xihua small high-speed mixer XH-422-10A) for physical stirring at a ratio of 1:40. The mixture was discharged after 5 minutes to obtain the final product.
[0090] Comparative Example 5
[0091] Instead of using a polymerization method, the pretreated zeolite is added after the polymerization process.
[0092] First, zeolite (Ningbo Jiahe New Materials, polished to 300 mesh by ourselves) was modified. 100 kg zeolite and 1 kg stearic acid (Sven SA1801, Indonesia) were placed in a mixing pot (Xihua small high-speed mixer XH-422-10A) respectively, physically stirred at 80 °C, and taken out after 5 minutes.
[0093] Afterwards, 100 g of the pretreated zeolite was directly physically stirred with 4 kg of the PVC resin obtained in Comparative Example 1 in a mixing pot (Xihua small high-speed mixer XH-422-10A) at a ratio of 1:40. The mixture was discharged after 5 minutes to obtain the final product.
[0094] After obtaining the resin, the ultraviolet light absorption value of the resin was tested according to the national standards GB / T15593-2020 and GB / T14233.1-2008. The test results are as follows.
[0095]
[0096] From the results, it can be seen that when a pre-treated porous adsorbent material (white carbon or zeolite, or activated carbon) is added during the polymerization process, its final water-extracted ultraviolet absorption performance is significantly better than that of ordinary PVC resin, as well as resins that are not pre-treated with porous adsorbent materials during the polymerization process, or resins that are later added with pre-treated porous adsorbent materials. This proves that the polyvinyl chloride resin prepared by the present invention has lower ultraviolet light absorption performance.
Claims
1. A polyvinyl chloride resin prepared by a method comprising the following steps: (1) providing a pretreated porous adsorbent material, wherein the pretreatment comprises treating the porous adsorbent material with a modifier having a polar group; (2) Adding the pretreated porous adsorbent material during the polymerization of polyvinyl chloride.
2. The polyvinyl chloride resin according to claim 1, wherein The porous adsorption material is selected from white carbon black, zeolite (molecular sieve), activated carbon or a combination thereof.
3. The polyvinyl chloride resin according to claim 1, wherein The white carbon black is selected from precipitated silica, fumed silica, ultrafine silica gel, powdered synthetic aluminum silicate and calcium silicate; preferably, the white carbon black is a porous substance, and its composition is represented by SiO2·nH2O, where n represents 1-10, wherein nH2O exists in the form of surface hydroxyl groups; or The zeolite is selected from the group consisting of clinoptilolite, mordenite, chabazite, erionite, phillipsite, heulandite, lauzenite, stilbite, chabazite, calcite, natrolite and analcime; or The activated carbon is selected from granular activated carbon, powdered activated carbon or columnar activated carbon, preferably powdered activated carbon; or, the activated carbon is selected from coal-based activated carbon, wood-based activated carbon or fruit shell-based activated carbon, preferably wood-based activated carbon; or, the mesh number of the activated carbon is greater than or equal to 60 meshes, preferably greater than or equal to 100 meshes, more preferably greater than or equal to 200 meshes, for example 60-400 meshes.
4. The polyvinyl chloride resin according to claim 1, wherein The modifier having a polar group includes fatty acid amide, fatty acid, alcohol, oxidized wax or a combination thereof; or, The fatty acid amide includes C2-C30 fatty acid amide, such as C6-C25 fatty acid amide; or, The fatty acid amides include butyric acid amide, caproic acid amide, capric acid amide, dodecanoic acid (lauric acid) amide, myristic acid (myristic acid) amide, hexadecanoic acid (palmitic acid) amide, octadecanoic acid (stearic acid) amide, eicosanoic acid (arachidic acid) amide, myristoleic acid amide, palmitic acid amide, rapeseed oil amide, linolenic acid amide, linolenic acid amide, oleic acid amide or a combination thereof; or, The fatty acid includes C2-C30 fatty acid, such as C6-C25 fatty acid; or, The fatty acids include butyric acid, caproic acid, caprylic acid, capric acid, dodecanoic acid (lauric acid), tetradecanoic acid (myristic acid), hexadecanoic acid (palmitic acid), octadecanoic acid (stearic acid), eicosanoic acid (arachidic acid), myristoleic acid, palmitoleic acid, rapeseed oleic acid, linolenic acid, linoleic acid, oleic acid or a combination thereof; or, The alcohol includes C1-C20 alkyl monoalcohol (e.g., C1-C10 alkyl alcohol, C1-C6 alkyl monoalcohol), C2-C20 alkyl diol (e.g., C2-C10 alkyl diol, C2-C6 alkyl diol), C3-C20 alkyl triol (e.g., C3-C10 alkyl triol, C3-C6 alkyl triol), C4-C20 alkyl tetraol (e.g., C4-C10 alkyl tetraol, C4-C8 alkyl tetraol) or a combination thereof; or The alcohol includes methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol, butanol, butanediol, pentanol, pentanediol, hexanol, hexanediol, pentaerythritol or a combination thereof; or, The oxidized wax includes oxidized paraffin (eg, oxidized liquid paraffin or oxidized solid paraffin), oxidized polyethylene wax or a combination thereof.
5. The polyvinyl chloride resin according to claim 1, wherein Based on 100 parts by weight of the porous adsorbent material, the amount of the modifier having a polar group is 0.05-20 parts by weight, such as 0.1-15 parts by weight, preferably 0.02-10 parts by weight, usually 0.5-5 parts by weight, and more preferably 1-2 parts by weight.
6. The polyvinyl chloride resin according to claim 1, wherein The method of treating the porous adsorbent material with a modifier having a polar group includes mixing, ultrasound or a combination thereof; alternatively, the treatment is carried out under heating conditions, such as 40-250°C, generally 50-200°C, preferably 60-150°C, and more preferably 80-120°C.
7. The polyvinyl chloride resin according to claim 1, wherein The pretreated porous adsorbent is pre-mixed with vinyl chloride monomer and an auxiliary agent and then the vinyl chloride monomer is polymerized, or the pretreated porous adsorbent is added during the polymerization of the vinyl chloride monomer.
8. The polyvinyl chloride resin according to claim 1, wherein Based on 100 parts by weight of vinyl chloride monomer, the amount of the pretreated porous adsorbent material is 0.1-20 parts by weight, such as 0.2-15 parts by weight, generally 0.5-10 parts by weight, preferably 1-5 parts by weight, and more preferably 1-2 parts by weight.
9. A product prepared from the polyvinyl chloride resin according to any one of claims 1 to 8.
10. A method for preparing a polyvinyl chloride resin, the method comprising the following steps: (1) providing a pretreated porous adsorbent material, wherein the pretreatment comprises treating the porous adsorbent material with a modifier having a polar group; (2) Adding the pretreated porous adsorbent material during the polymerization of polyvinyl chloride.
